A cross‐fostering analysis of bromine ion concentration in rats that inhaled 1‐bromopropane vapor. Issue 3 (16th June 2016) - Ishidao, Toru; Fueta, Yukiko; Ueno, Susumu; Yoshida, Yasuhiro; Hori, Hajime
Abstract : Objective: Inhaled 1‐bromopropane decomposes easily and releases bromine ion. However, the kinetics and transfer of bromine ion into the next generation have not been clarified. In this work, the kinetics of bromine ion transfer to the next generation was investigated by using cross‐fostering analysis and a one‐compartment model. Methods: Pregnant Wistar rats were exposed to 700 ppm of 1‐bromopropane vapor for 6 h per day during gestation days (GDs) 1‐20. After birth, cross‐fostering was performed between mother exposure groups and mother control groups, and the pups were subdivided into the following four groups: exposure group, postnatal exposure group, gestation exposure group, and control group. Bromine ion concentrations in the brain were measured temporally. Results: Bromine ion concentrations in mother rats were lower than those in virgin rats, and the concentrations in fetuses were higher than those in mothers on GD20. In the postnatal period, the concentrations in the gestation exposure group decreased with time, and the biological half‐life was 3.1 days. Conversely, bromine ion concentration in the postnatal exposure group increased until postnatal day 4 and then decreased. This tendency was also observed in the exposure group. A one‐compartment model was applied to analyze the behavior of bromine ion concentration in the brain. By taking into account the increase of body weight and change in the bromine ion uptake rate in pups, the bromine ion concentrations in the brains of the rats could be estimated with acceptable precision.